Three-dimensional dynamics focusing on lower trunk motion in the horizontal plane during sprinting - Ohshima, Y.; Fujii, N. (Japan Journal of Physical Education, Health and Sport Sciences, 2016)
The purpose of this study was to clarify the function of torques exerted by the joints of the lower trunk during maximal velocity sprinting. Eight male track and field athletes volunteered, and sprinted 60 m from a standing start position. The ground reaction force of the support leg was determined using a force platform (1000 Hz), which was placed at the 50-m mark from the start position. Simultaneously, 3D coordinates were recorded with a motion analysis system (250 Hz) using 20 cameras (MX-T20). The joint torques were calculated using inverse dynamics. The contribution of joint torques to the right and left hip joint forces, and the torso joint force, was calculated by a method that simultaneously solves equations of motion for each segment and equations of constraint conditions for adjacent segments connected by a joint. The main results were as follows: (1) During the terminal support phase (80-100% normalized time), the angular velocity of anterior rotation of the pelvis decreased and participants in whom this angular velocity decrease was diminished ran faster (p<0.10). (2) During terminal support, the hip joint adduction torque of the support leg and the anterior rotation torque of the torso joint rotated the pelvis forward. The moment of the right and left hip joint forces rotated the pelvis backward. (3) During terminal support, the hip joint force of the support leg was generated by its hip joint flexion and adduction torque, the hip joint extension torque of the recovery leg, and the anterior rotation torque of the torso joint. In contrast, the hip joint force of the recovery leg was generated by the hip joint flexion and adduction torque of the support leg, and the anterior rotation torque of the torso joint. (4) During terminal support, the hip joint flexion torque exerted by the support leg rotated the pelvis backward. The hip joint adduction torque of the support leg and the anterior rotation torque of the torso joint rotated the pelvis forward. Previous studies showed that the hip flexion torque drives the leg forward from the hip joint extension position. This present study has clarified that the hip joint adduction torque of the support leg and the anterior rotation torque of the torso joint nullify backward rotation of the pelvis due to the hip joint flexion torque exerted by the support leg.